Minerals and Phytic Acid Content in Different Varieties of Rice and their Changes due to Traditional Cooking Methods - Chowdhury, Nuzhat; Rahman, Mustafizur; Sayeed, Sultana (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.85-94